(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
The rapid advancement of information technology in the digital era has significantly changed how professionals operate across various fields, while also introducing new ethical challenges. This study aims to examine how information technology affects the implementation of professional ethics using a Systematic Literature Review (SLR) approach. The review was conducted by analyzing relevant scholarly articles sourced from Google Scholar and Garuda Jurnal databases. Findings indicate that information technology supports ethical practices by enhancing transparency, efficiency, and accountability within professional environments. Nonetheless, it also raises emerging ethical concerns, including data misuse, privacy breaches, and the widespread circulation of false information or hoaxes. These developments necessitate a strong sense of ethical awareness and the ability to adapt to technological changes, enabling professionals to perform their roles responsibly. The study concludes that the integration of ethical understanding with digital competency is essential for fostering a professional, ethical, and sustainable workplace in the digital era. Pesatnya perkembangan teknologi informasi di era digital telah mengubah cara kerja para profesional di berbagai bidang, sekaligus memunculkan tantangan baru dalam penerapan etika profesi. Penelitian ini bertujuan untuk menganalisis bagaimana peran teknologi informasi memengaruhi pelaksanaan etika profesi melalui pendekatan Systematic Literature Review (SLR). Kajian dilakukan dengan menelusuri artikel-artikel ilmiah yang relevan dari basis data Google Scholar dan Garuda Jurnal. Hasil kajian menunjukkan bahwa teknologi informasi berperan dalam memperkuat penerapan etika, seperti meningkatkan transparansi, efisiensi, dan akuntabilitas dalam praktik profesional. Namun, teknologi juga memunculkan isu-isu etis baru, seperti penyalahgunaan data, pelanggaran privasi, dan penyebaran informasi palsu atau hoaks. Oleh karena itu, diperlukan kesadaran etis yang tinggi serta kemampuan adaptasi terhadap kemajuan teknologi agar profesional dapat menjalankan perannya secara bertanggung jawab. Kajian ini menyimpulkan bahwa integrasi antara pemahaman etika profesi dan penguasaan teknologi informasi sangat penting dalam menciptakan lingkungan kerja yang etis, profesional, dan berkelanjutan di era digital.